(untitled) (mathematica didactica, 2005)
In analysis lessons the expression „Kurvendiskussion“ is confusing because it often refers less to curves than to graphs of functions, and instead of a discussion there should be given calculations using rules to be acquainted with. By means of examples we show in his article that it is reasonable and possible to draw learners’ attention to graphs having different genesis and forms. As we know from experience, in this way their motivation can be fostered by asking questions by themselves and discussing productively. Such discussions about concepts, methods and strategies also help to develop and strengthen the mathematical skill of learners.